Six years after the EU-Turkey Agreement: A quantitative assessment of the living conditions of Syrians in Turkey - Lidwina Gundacker; Laura Hertner; Simon Ruhnke (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2024)
According to the German Federal Statistical Office, 2.9 million people in Germany had a Turkish migration background in 2022. Thus, Turkey represents one of the most important countries of origin for migrants in Germany. In the last decade, however, Turkey has also become an important transit and destination country for migrants itself. Since 2011, when war broke out in Syria, more than 3.7 million Syrians have sought refuge in Turkey. Starting in 2014, Turkey's initial open-door immigration policy increasingly gave way to restrictive measures with the goal to limit migration from Syria. Following a German initiative, the European Union (EU) and the Turkish government agreed on a migration agreement in 2016. The EU-Turkey agreement aimed at limiting irregular migration to the EU and, in turn, improving the humanitarian conditions for refugees in Turkey by providing 6 billion Euros in aid. [...] – – 2,9 Millionen Personen in Deutschland hatten im Jahr 2022 laut dem Statistischen Bundesamt einen türkischen Migrationshintergrund. Somit stellt die Türkei seit Jahrzehnten eins der wichtigsten Herkunftsländer von Migrant*innen in Deutschland dar. Im letzten Jahrzehnt hat sich die Türkei allerdings selbst zu einem wichtigen Transit- und Zielland für Zugewanderte entwickelt. Seit 2011, dem Beginn des Krieges in Syrien, haben mehr als 3,5 Millionen Syrerinnen und Syrer Zuflucht in der Türkei gesucht. Die zunächst offen gestaltete türkische Einwanderungspolitik wich ab 2014 zunehmend Maßnahmen, die Zuwanderung aus Syrien zu begrenzen. Vorangetrieben von Deutschland beschlossen die Europäische Union (EU) und die türkische Regierung im Jahr 2016 ein Rückübernahmeabkommen. Das EU-Türkei-Abkommen verfolgte das Ziel, irreguläre Migration in die EU zu begrenzen und im Gegenzug die humanitären Bedingungen für Geflüchtete in der Türkei durch Hilfsgelder in Milliardenhöhe zu verbessern. [...]
Keywords: 330; Syrien; Türkei; berufliche Integration; Bildungsbeteiligung; Einkommenshöhe; Einwanderungsland; Einwanderungspolitik; Europäische Union; Geflüchtete; Flüchtlingsfürsorge; Herkunftsland; Inländer; internationale Zusammenarbeit; Lebenssituation; prekäre Beschäftigung; schulische Integration; Sprachkenntnisse; Türkisch; 2021-2022